2019
DOI: 10.1111/adb.12799
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double‐blind, placebo‐controlled study of the kappa opioid receptor antagonist, CERC‐501, in a human laboratory model of smoking behavior

Abstract: Preclinical data indicate that selective kappa opioid receptor antagonists reduce nicotine self‐administration and withdrawal symptoms. The aim of the current study was to determine whether treatment with CERC‐501, an orally available, potent, and selective kappa opioid receptor antagonist, could alleviate nicotine withdrawal and craving and mitigate mood alterations associated with nicotine withdrawal in humans. Healthy, adult cigarette smokers were enrolled into this randomized, multisite, double‐blind, plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Of translational relevance, the antagonist LY2795050 is used as a κ-receptor radiotracer in humans (de Laat et al, 2019; Naganawa et al, 2015a), and some studies have detected decreased occupancy in several brain regions in female compared to male humans (Vijay et al, 2016). Novel short-acting κ-antagonists have reached the clinical investigation stage, for example in persons with cocaine or tobacco use disorders, as well as mood disorders (Guerrero et al, 2019a; Jacobson et al, 2020a; Jones et al, 2019; Reed et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of translational relevance, the antagonist LY2795050 is used as a κ-receptor radiotracer in humans (de Laat et al, 2019; Naganawa et al, 2015a), and some studies have detected decreased occupancy in several brain regions in female compared to male humans (Vijay et al, 2016). Novel short-acting κ-antagonists have reached the clinical investigation stage, for example in persons with cocaine or tobacco use disorders, as well as mood disorders (Guerrero et al, 2019a; Jacobson et al, 2020a; Jones et al, 2019; Reed et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, structurally novel κ-antagonists have been described with rapid onset (e.g., approximately 30 min) and moderate durations of action (e.g., approximately 24 h) in vivo (Guerrero et al, 2019b; Rorick-Kehn et al, 2014). Several compounds of this type, including LY2456302 (also known as CERC-501 or aticaprant) ((S)-3-fluoro-4-(4-((2 (3,5-dimethylphenyl)pyrrolidin-1-yl)methyl)phenoxy) benzamide), have been examined in humans, including normal volunteers, as well as persons with specific psychiatric diagnoses, such as cocaine dependence (Chang et al, 2011; Guerrero et al, 2019b; Jones et al, 2019; Lowe et al, 2014; Naganawa et al, 2015a; Reed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CERC-501 (i.e. LY2456301) failed to attenuate cigarette smoking, craving, or nicotine withdrawal in humans (Jones et al 2019). Moreover, a recent positron emission tomography study examining KOR binding in healthy controls and cocaine abusers reported no significant differences in KOR binding in any brain region examined (Martinez et al 2019).…”
Section: Kor Antagonist Effects On Human Drug Sa Metricsmentioning
confidence: 99%
“…CERC-501, used in phase 1 clinical trials, does not share nor-BNI or JDTic pharmacological properties ( Carroll and Carlezon, 2013 ; Jacobson et al, 2020 ). Nevertheless, this last compound, a KOR antagonist that have low affinities for MOR and DOR ( Banks, 2020 ), failed to attenuate cocaine craving ( Reed et al, 2018 ), or cigarette smoking and craving ( Jones et al, 2020 ).…”
Section: The Dynorphin/kappa-opioid Receptor Systemmentioning
confidence: 99%